World Development Report 1988 - World Bank (New York: Oxford University Press, 2012)
This is the eleventh report in the annual series assessing major development issues. Part I reviews recent trends in the world economy and their implications for the future prospects of developing countries. Part II examines the role of public finance in development. This report includes the World Development Indicators, which provide selected social and economic indicators for more than 100 countries. Despite continued economic growth through 1987 and into 1988, two problems have characterized recent trends: unsustainable economic imbalances within and among industrial countries, and highly uneven economic growth among developing countries. Part I of the report concludes that three interdependent policy challenges need to be addressed. First, industrial countries need to reduce their external payments imbalances. Second, developing countries need to continue restructuring their domestic economic policies in order to gain creditworthiness and growth. Third, net resource transfers, external debt, from the developing countries must be trimmed so that investment and growth can resume. Part II of the report explores how public finance policies are best designed and implemented. How deficits are reduced is crucial: controlling costs in mobilizing revenues and setting careful priorities in public spending are equally important. Efficiency in providing public services and expanding the scope for raising revenue can be achieved through decentralizing decisionmaking and reforming state-owned enterprises with the latter permitting greater private participation.